Development of Augmented Reality media in polyhedral space-building lessons to improve the mathematical reasoning ability - Hanna Arsyinta Prayoga; Megita Dwi Pamungkas; Arifta Nurjanah (Universitas Sarjanawiyata Tamansiswa, 2024)
Technology plays a crucial role in education, especially in supporting teachers with interactive media to enhance students' mathematical reasoning in polyhedral geometry. This study aims to improve students' mathematical reasoning by developing and utilizing valid, practical, and effective augmented reality (AR) media for polyhedral geometry. The research adopts the ADDIE development model. The validity test results of the developed media indicate a validity score of 81.79% for media and 78.33% for material, categorized as highly valid. The practicality analysis, based on student response questionnaires, yields a score of 79.08%, categorized as practical. The effectiveness analysis, based on pretest and posttest data analyzed using the Paired Sample T-test, reveals a significant value of 0.000, indicating a significant improvement in students' average scores. Furthermore, the N-Gain score of 0.64 falls into the moderate category, confirming the media's effectiveness in enhancing mathematical reasoning. In conclusion, the augmented reality learning media for polyhedral geometry is valid, practical, and effective in improving students' mathematical reasoning. Future research is encouraged to develop more innovative products to further enhance learning quality.